Investigating the role of the Renin Angiotensin System in cancer - Dunn, Cherise (Division of Medical Microbiology, 2018)
It has recently been discovered that cancer shares a link with metabolic diseases, including that of cardiovascular disease, diabetes, amongst others, where common sets of genes show similar gene expression. There is thus interest to investigate current therapies for metabolic diseases as possible anti-cancer agents. The renin-angiotensin system (RAS) regulates blood pressure and cardiovascular homeostasis through Angiotensin Converting Enzyme-1 (ACE-1) and its homolog ACE-2. RAS has also been implicated in the progression of various cancers due to the increased action of the vasoconstrictor, angiotensin II, which requires ACE-1 and specifically the Angiotensin Type 1 Receptor (AT1R) for its function. In this study, we investigated the potential association of the endogenous ACE-1 and ACE-2 enzymes in cervical cancer. Our results showed that ACE-1 and AT1R protein expression was elevated in cervical cancer cell lines compared to normal cells and that this correlated with elevated ACE-1 enzyme activity in cancer cells. Treatment with the ACE-1 inhibitors, Captopril and Lisinopril, reduced this activity. We showed that ACE-1 axis stimulation in cancer cells results in increased calcium signaling preferentially via the AT1R and this associates with cancer cell proliferation. Candesartan, an AT1R blocker significantly reduced these effects. ACE-2 expression and activity were decreased in cancer compared to normal cells. Our data shows that ACE2 activators, the natural peptide angiotensin 1-7 and small molecule Diminazene aceturate (DIZE) have anticancer effects with DIZE inducing a G2/M arrest in cancer cells. We also investigated associations between drugs targeting RAS and current chemotherapeutic agents, Cisplatin (CDDP) and Doxorubicin (DOX). Our data shows that ACE-1 axis inhibitors have an antagonistic effect on CDDP, while the ACE-2 activator DIZE associates synergistically with DOX. Taken together, these results suggest that elevated ACE- 1 expression associates with cervical cancer and that the inhibitors of ACE-1 function or activators of ACE-2 function have potential as anticancer therapies as single agents or in combination treatments with current chemotherapeutics.